Implementasi Reorientasi Pasien Delirium Melalui Rekaman Suara Keluarga di Ruang ICU RSUD Prof. Dr. Margono Soekarjo: Case Study - Dicha Choirunnisa; Sidik Awaludin; Aji Kurniawan (Journal of Bionursing, 2019)
Background. Delirium in critically ill patients who have decreased consciousness is a case that’s found in the ICU. Disorientation and anxiety are common characteristics shown in delirium patients. Collaboration between nurses and patients can be done by giving reorientation through voice recording of family members in delirium patients in the ICU.Methods. Implementation is carried out using experimental studies with a pre-post control group. Six patients were selected by simple random sampling technique which was divided into three groups. The criteria for patients in implementation included, patients aged > 18 years, entering the ICU within ? 24 hours, and positive delirium based on the score of the Confusion Assessment Method for the ICU (CAM-ICU) assessment.Results. There was a change in the family voice intervention group with an RASS rating scale. But in the three groups, patients were still diagnosed with delirium positive after being given an implementation based on the CAM-ICU rating scale.Conclusion. Giving reoriented message recordings using family voice can be used to reduce symptoms of delirium in patients undergoing treatment in the ICU.